A high-insulation and high-thermal-conductivity rebound thermally conductive gasket and a preparation method thereof

By adding fibrous aluminum nitride single crystals and inorganic spherical powder to the raw materials of the thermal gasket, and using the crosslinking reaction of silicone oil, the problem of the thermal conductivity and insulation properties of the thermal conductivity gasket cannot be taken into account, achieving high thermal conductivity, high rebound and high insulation effects.

CN119775779APending Publication Date: 2025-04-08SUZHOU TECHNO NEW MATERIAL TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411617387.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-26
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

Existing thermal conductivity gaskets often cannot take into account both thermal conductivity and insulation performance, or have poor rebound performance, which affects their heat dissipation effect and service life.

Method used

By adding fibrous aluminum nitride single crystals to the raw materials of the rebound thermal gasket to reinforce and reduce internal friction, combined with the cross-linking reaction of vinyl silicone oil, end-hydrogen silicone oil and side-hydrogen silicone oil, a high thermal conductivity, high rebound and high insulation material is formed.

Benefits of technology

It achieves a balance between high thermal conductivity and high rebound performance, while improving the strength and toughness of the material, extending service life, and maintaining good performance under complex stress environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005132594960000051
    Figure BDA0005132594960000051
  • Figure BDA0005132594960000061
    Figure BDA0005132594960000061
  • Figure HDA0005287847500000011
    Figure HDA0005287847500000011
Patent Text Reader

Abstract

The present application provides a high-insulation and high-thermal-conductivity rebound thermally conductive gasket and a preparation method thereof, and relates to the technical field of thermal interface materials. The thermally conductive gasket includes the following raw materials: silicone oil, MQ resin, inorganic spherical powder, fibrous aluminum nitride single crystal, platinum catalyst, and inhibitor. The preparation method includes: mixing inorganic spherical powder with fibrous aluminum nitride single crystal to form a thermally conductive filler; first dispersing silicone oil, MQ resin and inhibitor, and then adding platinum catalyst for secondary dispersion to obtain a matrix liquid; mixing the thermally conductive filler with the matrix liquid evenly to obtain a semi-finished raw rubber; calendering the semi-finished raw rubber or introducing it into a mold for pressing to make a high-insulation and high-thermal-conductivity rebound thermally conductive gasket. The present application adds fibrous aluminum nitride single crystals and inorganic spherical powder to the raw materials of the rebound thermally conductive gasket to reinforce and reduce internal friction while having high thermal conductivity, and then combines with the high elasticity of MQ resin to achieve a high rebound effect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of thermal interface materials, and in particular to a high-insulation and high-thermal-conductivity rebound thermally conductive gasket and a preparation method thereof. Background Art

[0002] As electronic devices become more high-performance and miniaturized, their heat generation power continues to increase, and the requirements for heat dissipation are becoming increasingly higher. As an effective thermal interface material, thermal conductive gaskets are widely used in the heat dissipation system of electronic devices. However, existing thermal conductive gaskets often have problems such as poor thermal conductivity and insulation performance, or poor rebound performance, which affects their heat dissipation effect and service life. Summary of the invention

[0003] In order to improve the problem that existing thermal conductive gaskets often have the problem of not being able to take both thermal conductivity and insulation performance into consideration, or having poor rebound performance, the present application provides a high-insulation and high-thermal-conductivity rebound thermal conductive gasket and a preparation method thereof.

[0004] In the first aspect, the present application provides a high-insulation and high-thermal-conductivity rebound thermally conductive gasket, which adopts the following technical scheme: a high-insulation and high-thermal-conductivity rebound thermally conductive gasket, comprising the following raw materials in parts by weight: 11.1-17.2 parts of silicone oil, 2-4 parts of MQ resin, 60-75 parts of inorganic spherical powder, 5-20 parts of fibrous aluminum nitride single crystals, 0.1-0.5 parts of platinum catalyst, and 0.3-0.8 parts of inhibitor.

[0005] The present application adds fibrous aluminum nitride single crystals and inorganic spherical powders to the raw materials of the rebound thermal conductive gasket to reinforce and reduce internal friction while having high thermal conductivity, and then combines the high elasticity of MQ resin to achieve a high rebound effect.

[0006] If the thermal conductive filler uses spherical powder to achieve high thermal conductivity, the powder needs to be piled up to increase the thermal conductivity path and reduce the interfacial thermal resistance between the powders. In this case, the material filling amount is high, while the matrix resin amount is small, which easily leads to increased internal friction between the powders, and then leads to a decrease in the overall strength of the material, and a lack of elasticity and toughness. If the thermal conductive filler uses fibrous aluminum nitride single crystals, although it can improve the overall strength and elasticity of the material, due to its small addition amount, the distribution of the fibrous aluminum nitride single crystals is relatively scattered, so the overall thermal conductivity path is relatively small, so its thermal conductivity is also relatively limited.

[0007] The present application adopts the method of cooperating with inorganic spherical powder and fibrous aluminum nitride single crystal. Since the fibrous aluminum nitride single crystal is larger in size, it is easier to contact with the inorganic spherical powder, so it can form more heat conduction pathways, thereby achieving both higher thermal conductivity and resilience with a smaller amount of thermal conductive filler added.

[0008] Optionally, the silicone oil includes vinyl silicone oil, terminal hydrogen silicone oil and pendant hydrogen silicone oil in a mass ratio of 10-15:0.8-1.2:0.3-1.

[0009] The present application adopts vinyl silicone oil as the main component, and its side chain with active vinyl groups can react with hydrogen-containing silicone oil under the action of a catalyst to undergo a hydrosilicification reaction, thereby cross-linking. This cross-linking reaction helps to form a stable three-dimensional network structure, enhancing the strength and resilience of the thermally conductive pad. Moreover, the vinyl silicone oil itself also has certain thermal conductivity and insulation properties, providing a good basis for preparing a high-insulation and high-thermal-conductivity rebound thermally conductive pad. And the end hydrogen silicone oil, because it contains a silicon-hydrogen bond at the end, is more likely to react with the vinyl in the vinyl silicone oil in the presence of a catalyst to undergo a hydrosilicification reaction, thereby participating in the preparation process of the thermally conductive pad as a cross-linking agent. The silicon-hydrogen bond in the side hydrogen silicone oil is located on the side chain of the polysiloxane chain, so it can also participate in the above-mentioned cross-linking reaction, further enriching the structure of the cross-linked network. At the same time, the bonding point formed by the silicon-hydrogen bond in the side hydrogen silicone oil in the cross-linking reaction may have better flexibility, which helps to improve the elasticity and resilience of the thermally conductive pad. Therefore, the present application improves the comprehensive performance of the thermally conductive pad by the mutual cooperation of the above three silicone oils.

[0010] Optionally, the inorganic spherical powder is selected from spherical alumina, spherical aluminum nitride, and spherical diamond.

[0011] The inorganic spherical powders selected in the present application have extremely high thermal conductivity, can quickly conduct heat, and their spherical structure effectively reduces the contact thermal resistance between particles, further improving the overall thermal conductivity of the gasket. At the same time, the spherical particles also give the gasket good mechanical strength and compression resistance, making the gasket difficult to deform or break when subjected to external forces. In addition, these inorganic particles also have good chemical stability and insulation, ensuring the reliability and durability of the thermally conductive gasket in a complex working environment.

[0012] Optionally, the inorganic spherical powder has a particle size of 0.5-120 μm, and the fibrous aluminum nitride single crystal has a length of 100 μm and a diameter of 1-3 μm.

[0013] The present application further limits the particle size of the inorganic spherical powder. The moderate particle size distribution enables the particles to form a compact stacking structure, reducing obstacles on the heat conduction path, thereby improving the thermal conductivity of the gasket.

[0014] The fibrous aluminum nitride single crystal used in the present invention not only has high thermal conductivity, but its unique fiber morphology also brings additional performance advantages to the gasket. This application uses fibrous aluminum nitride single crystals of the above length and diameter. The large aspect ratio of the fibrous aluminum nitride single crystal allows the fibrous aluminum nitride single crystal to form an effective thermal conductive network with the inorganic spherical powder, and construct a channel for rapid heat conduction inside the gasket. This network structure not only improves the thermal conductivity of the gasket, but also enhances the thermal shock resistance and crack resistance of the gasket. In addition, the addition of fibrous aluminum nitride single crystals also improves the mechanical strength and toughness of the gasket, allowing it to maintain good resilience and durability under complex stress environments.

[0015] Optionally, the inorganic spherical powder includes large-particle powder with a particle size range of 80-120 μm, medium-particle powder with a particle size range of 2-10 μm and small-particle powder with a particle size range of 0.4-0.8 μm, and the mass ratio of the three is 6-7:4-6:2.

[0016] The present application limits the inorganic spherical powder to different particle size ranges, which can significantly improve the thermal conductivity of the gasket through the filling effect and the increase of contact points between particles. At the same time, the spherical particles also help to reduce stress concentration and maintain the resilience of the gasket.

[0017] Optionally, 0.5-1.5 parts of a coupling agent are also included.

[0018] Optionally, the coupling agent is a silane coupling agent containing vinyl and methoxy groups.

[0019] The present application also adds a coupling agent to the raw materials of the thermally conductive gasket, which can effectively bridge the interface between the inorganic filler and the organic matrix and enhance the interaction between them. This enhanced interfacial bonding force not only improves the overall performance stability of the gasket, but also promotes the effective transfer of heat, further improving the thermal conductivity of the gasket. At the same time, the addition of the coupling agent also helps to improve the processing fluidity and formability of the gasket, making it easier to operate and control during the production process.

[0020] In a second aspect, the present application provides a method for preparing a high-insulation and high-thermal-conductivity resilient thermally conductive gasket, using the following technical solution: A method for preparing the high-insulation and high-thermal-conductivity rebound thermally conductive gasket comprises the following steps: Step S1: Mixing inorganic spherical powder and fibrous aluminum nitride single crystal to form a thermal conductive filler; Step S2: Dispersing the silicone oil, MQ resin and inhibitor once, and then adding a platinum catalyst for secondary dispersion to obtain a matrix liquid; Step S3: uniformly mixing the thermal conductive filler and the base liquid to obtain a semi-finished raw rubber; Step S4: calendaring the semi-finished raw rubber or introducing it into a mold for pressing to produce the high-insulation and high-thermal-conductivity rebound thermally conductive gasket.

[0021] Optionally, the step S1 further includes the following steps: drying the thermally conductive filler and uniformly dispersing the thermally conductive filler with a coupling agent to obtain a pretreated thermally conductive filler.

[0022] The present application uses a coupling agent to pre-treat the thermally conductive filler, which can further enhance the interfacial bonding force between the thermally conductive filler and the matrix liquid, so that the thermally conductive filler is more stably distributed in the matrix liquid. This pre-treatment not only improves the overall performance stability of the gasket, but also extends its service life. In addition, the pre-treated filler is easier to mix evenly with the matrix liquid, reducing difficulties and problems in the production process and improving production efficiency and yield rate.

[0023] Optionally, the specific operation of step S3 is as follows: the thermal conductive filler is gradually added to the base liquid for three times for mixing, and the entire mixing process is performed under vacuum conditions.

[0024] The present application uses a batch-wise addition method to mix the thermal conductive filler with the base liquid, which can promote a more complete and uniform mixing of the two, ensuring the uniformity and density of the internal structure of the gasket, and the entire mixing process is carried out under vacuum conditions, effectively avoiding the generation of bubbles and impurities. In addition, mixing under vacuum conditions also ensures that the gasket is not prone to air gaps or thermal resistance points during use, further improving its stability and reliability.

[0025] In summary, the present application includes at least one of the following beneficial effects: 1. The present application adds fibrous aluminum nitride single crystals and inorganic spherical powders to the raw materials of the rebound thermal conductive gasket to reinforce and reduce internal friction while having high thermal conductivity, and then combines the high elasticity of MQ resin to achieve a high rebound effect.

[0026] 2. The present application limits the inorganic spherical powder to different particle size ranges, which can significantly improve the thermal conductivity of the gasket through the filling effect and the increase in contact points between particles. At the same time, the spherical particles also help to reduce stress concentration and maintain the resilience of the gasket. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 It is a schematic diagram of a high-insulation and high-thermal-conductivity rebound thermally conductive gasket according to the present application. DETAILED DESCRIPTION

[0028] The present invention is further described below in conjunction with specific embodiments. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0029] The vinyl silicone oil used in the following examples and comparative examples is Andisil VS1000LC CV, wherein the vinyl content is 0.11 mmoles / g and the viscosity at 25° C. is 1000 cst.

[0030] The hydrogen-terminated silicone oil used in the following examples and comparative examples is Andisil CE 30LV, in which the hydrogen content is 0.75 mmole / g and the viscosity at 25° C. is 50 cst.

[0031] The side hydrogen silicone oil used in the following examples and comparative examples is Andisil XL-1340, wherein the hydrogen content is 3.00 mmole / g and the viscosity at 25° C. is 50 cst.

[0032] The MQ resin used in the following examples and comparative examples is Andisil VQM 2050, wherein the vinyl content is 1.10 mmoles / g and the viscosity at 25° C. is 500 cst.

[0033] The platinum catalyst used in the following examples and comparative examples is a Custer platinum catalyst with a platinum content of 5000 ppm.

[0034] The coupling agent used in the following examples and comparative examples is vinyltrimethoxysilane.

[0035] The inhibitor used in the following examples and comparative examples is an acetylene cyclohexanol inhibitor.

[0036] The fibrous aluminum nitride single crystals used in the following examples and comparative examples are from U-MAP Co., LTD. The long fiber product is about 100μm long and 1-3μm in diameter.

[0037] Example 1 Example 1 provides a high-insulation and high-thermal-conductivity resilient thermally conductive gasket, and the specific ingredients of the raw materials are shown in Table 1. The preparation method of the high-insulation and high-thermal-conductivity resilient thermally conductive gasket is as follows: Step S1: Mix an inorganic spherical powder (spherical aluminum nitride) with a fibrous aluminum nitride single crystal to form a thermally conductive filler, dry at 120° C. for 4 hours, and put the thermally conductive filler into a high-speed mixer after drying and natural cooling. Dilute the coupling agent with a mixed solution of ethanol and water (ethanol to water volume ratio of 1:1) to obtain a coupling agent solution with a mass fraction of 10%, spray the coupling agent solution into the thermally conductive filler to increase the contact area between the thermally conductive filler and the coupling agent solution to ensure that the two are in more complete contact, stir for another 3 hours, and then dry and cool to obtain a pretreated thermally conductive filler; Step S2: Dispersing silicone oil (vinyl silicone oil, terminal hydrogen silicone oil and pendant hydrogen silicone oil), MQ resin and inhibitor for 10 minutes, and then adding platinum catalyst for secondary dispersion for 10 minutes to obtain a matrix liquid; Step S3: first add 1 / 3 of the thermal conductive filler and the base liquid into a double planetary stirring kettle, mix for 60 minutes under vacuum conditions, then add the remaining thermal conductive filler twice, each time mixing for 60 minutes under vacuum conditions, and finally obtain a semi-finished raw rubber; Step S4: introducing the semi-finished raw rubber into the mold, pressing and vacuum curing at 150° C. for 30 minutes to produce a high-insulation and high-thermal-conductivity rebound thermal gasket.

[0038] Table 1 Example 2-3 Embodiment 2-3 is basically the same as embodiment 3, and the only difference is that the amount of raw materials used in each embodiment is different, as shown in Table 1.

[0039] Example 4 Example 4 is basically the same as Example 3, except that in Example 4, all spherical aluminum nitride within each particle size range in Example 3 is replaced with spherical aluminum oxide within the corresponding particle size range.

[0040] Example 5 Example 5 is basically the same as Example 1, except that in Example 5, all spherical aluminum nitrides within various particle size ranges in Example 3 are replaced with spherical diamonds within the corresponding particle size ranges.

[0041] Comparative Examples 1-3 Comparative Examples 1-3 are substantially the same as Example 3, except that the amounts of raw materials used in the comparative examples are different, as shown in Table 1.

[0042] Comparative Example 4 Comparative Example 4 is substantially the same as Example 3, except that in Comparative Example 4, the fibrous aluminum nitride single crystal in Example 3 is replaced with carbon fiber.

[0043] Performance Testing The following performance tests were performed on the thermally conductive pads prepared in the above Examples 1-5 and Comparative Examples 1-3, and the test methods were as follows. The test results are shown in Table 2.

[0044] 1. Thermal conductivity: Test thermal conductivity according to ASTM D 5470 standard; 2. Insulation: Dielectric strength is tested according to ASTM D 149 2009 standard; 3. Mechanical strength: Test tensile strength and elongation at break according to GB / T 1040.3; 4. Resilience: The rebound rate is tested according to ASTM D575-91 standard.

[0045] Table 2 It can be seen from the results in Table 2 that Examples 1-5 all exhibit good thermal conductivity, insulation, mechanical strength and resilience.

[0046] Compared with Example 3, Comparative Example 1 only uses spherical aluminum nitride as a thermally conductive filler. Due to the lack of fibrous aluminum nitride single crystals, more thermal conductive paths cannot be formed, resulting in a significant reduction in its thermal conductivity.

[0047] Compared with Example 3, Comparative Example 2 only uses fibrous aluminum nitride single crystals as thermally conductive filler, and the filling amount in the above Table 1 has reached the filling upper limit of the thermally conductive filler. However, since the type of thermally conductive filler in Comparative Example 2 is only fibrous aluminum nitride single crystals, its thermal conductivity is slightly lower than that of Example 3, and its elongation at break and rebound rate are also far inferior to those of Example 3, showing poor toughness and rebound performance.

[0048] Compared with Example 3, in Comparative Example 3, all the spherical aluminum nitride particles have a particle size in the range of 2-10 μm, so the contact points between the thermally conductive fillers are reduced, and the thermal conductive paths are correspondingly reduced, resulting in a decrease in its thermal conductivity.

[0049] Compared with Example 3, Comparative Example 4 uses carbon fiber to replace the fibrous aluminum nitride single crystal. The thermal conductivity, mechanical strength and resilience of the product are better. However, its insulation performance is much lower than that of Example 3.

[0050] The above are all preferred embodiments of the present application, and the protection scope of the present application is not limited thereto. Therefore, any equivalent changes made according to the structure, shape, and principle of the present application should be included in the protection scope of the present application.

Claims

1. A high insulation and high thermal conductivity rebound thermal pad, characterized in that: The invention comprises the following raw materials in parts by weight: 11.1-17.2 parts of silicone oil, 2-4 parts of MQ resin, 60-75 parts of inorganic spherical powder, 5-20 parts of fibrous aluminum nitride single crystal, 0.1-0.5 parts of platinum catalyst and 0.3-0.8 parts of inhibitor.

2. The high insulation and high thermal conductivity rebound thermally conductive gasket according to claim 1, characterized in that: The silicone oil comprises a mass ratio of 10-15: 0.8-1.2:0.3-1 vinyl silicone oil, terminal hydrogen silicone oil and side hydrogen silicone oil.

3. The high insulation and high thermal conductivity rebound thermally conductive gasket according to claim 1, characterized in that: The inorganic spherical powder is selected from spherical aluminum oxide, spherical aluminum nitride and spherical diamond.

4. The high insulation and high thermal conductivity rebound thermally conductive gasket according to claim 1, characterized in that: The particle size of the inorganic spherical powder is 0.5-120 μm, and the length of the fibrous aluminum nitride single crystal is 100 μm and the diameter is 1-3 μm.

5. The high insulation and high thermal conductivity rebound thermally conductive gasket according to claim 4, characterized in that: The inorganic spherical powder includes large-particle powder with a particle size range of 80-120 μm, medium-particle powder with a particle size range of 2-10 μm and small-particle powder with a particle size range of 0.4-0.8 μm, and the mass ratio of the three is 6-7:4-6:

2.

6. The high insulation and high thermal conductivity rebound thermally conductive gasket according to claim 1, characterized in that: Also included is 0.5-1.5 parts of a coupling agent.

7. The high insulation and high thermal conductivity rebound thermally conductive gasket according to claim 6, characterized in that: The coupling agent is a silane coupling agent containing vinyl and methoxy groups.

8. A method for preparing a high-insulation and high-thermal-conductivity rebound thermally conductive gasket according to any one of claims 1 to 5, characterized in that: The steps include: Step S1: Mixing inorganic spherical powder and fibrous aluminum nitride single crystal to form a thermal conductive filler; Step S2: Dispersing the silicone oil, MQ resin and inhibitor once, and then adding a platinum catalyst for secondary dispersion to obtain a matrix liquid; Step S3: uniformly mixing the thermal conductive filler and the base liquid to obtain a semi-finished raw rubber; Step S4: calendaring the semi-finished raw rubber or introducing it into a mold for pressing to produce the high-insulation and high-thermal-conductivity rebound thermally conductive gasket.

9. The method for preparing the high-insulation and high-thermal-conductivity rebound thermally conductive gasket according to claim 8, characterized in that: The step S1 also includes the following steps: drying the thermally conductive filler and uniformly dispersing the thermally conductive filler with a coupling agent to obtain a pretreated thermally conductive filler.

10. The method for preparing the high-insulation and high-thermal-conductivity rebound thermally conductive gasket according to claim 8, characterized in that: The specific operation of step S3 is as follows: the thermal conductive filler is gradually added into the base liquid for three times for mixing, and the entire mixing process is performed under vacuum conditions.